Incidence of COVID-19 on poverty, Huánuco Region, 2020 - Ubillus, Milward (2021)
Objective. To determine the relationship between the incidence of COVID-19 and poverty in the Huánuco Region during 2020. Method. This was a descriptive, ecological, multiple-group, cross-sectional, retrospective study. The population consisted of the 11 provinces and 84 geopolitical districts of the department of Huánuco. The type of sampling was non-random, purposive by convenience. Data from primary sources were used, such as the Report of New Cases of COVID-19 of the Regional Health Directorate - Huanuco - DIRESA 2020. Results. Regarding the number of new cases of COVID-19, the provinces of Huánuco, Leoncio Prado and Puerto Inca had the highest number of cases, while the provinces with the lowest number of new cases were Lauricocha, Yarowilca and Huacaybamba. Likewise, the provinces of Puerto Inca, Leoncio Prado and Huánuco had the highest incidence rates. When evaluating poverty in the department of Huanuco, the classification of poverty levels in each district carried out as of 2018 in INEI's 2018 Provincial and District Monetary Poverty Map was taken into account. The province of Leoncio Prado has the poorest districts, followed by the province of Huánuco and Lauricocha. The provinces with the least poor districts are Huacaybamba, Pachitea and Marañón. Conclusions. There is a statistically significant positive correlation of 0.646 for a p < 0.05 between the level of poverty and the incidence of Covid19 in Huánuco, during 2020.